Gaps and Runs in Nest Cavity Occupancy: Cavity “Destroyers” and “Cleaners” Affect Reuse by Secondary Cavity Nesting Vertebrates - Wiebe, Karen L.; Cockle, Kristina L.; Trzcinski, M. Kurtis; Edworthy, Amanda B.; Martin, Kathy (Frontiers in Ecology and Evolution, 2020)
Many animals require tree cavities for breeding and these sites may be reused by a diversity of secondary cavity nesters over a timespan of decades. It is unknown whether the reuse of holes changes their desirability as nest sites. We hypothesized that some species, "cavity destroyers", degraded the quality of holes by filling them with coarse nest material or waste whereas other species, "cavity cleaners", might prolong the use of a hole by removing debris or enlarging the hole. Using data gathered during 22 years from a field study in central British Colombia, we analyzed long-term patterns of cavity occupancy in relation to their sequential use by bird and mammal species, grouped by traits. Patterns of cavity occupancy were variable with 49% of 875 large-sized holes (excavated by northern flickers Colaptes auratus and pileated woodpeckers Dryocopus pileatus) and 19% of 672 smaller-sized holes incorporating runs of sequential use that lasted up to 18 years. But 11-25% of cavities also had gaps of 3-13 years between occupancies. Mammals, raptors and European starlings, consistent with the hypothesis they were cavity destroyers, occupied cavities as terminal users and before gaps more often than expected by chance. The pattern of occupancy by northern flickers was random in relation to gaps or prior use by other species so, although flickers did not target old holes to clean, neither did they avoid them. Small cavities that were renovated by flickers into larger cavities had double the reuse rate. Runs of cavity occupancy that involved only cavity-destroying species were shorter than runs that involved periodic use by flickers, suggesting the woodpecker, through its cleaning and renovation, prolonged the use of such holes.